PERSEPSI MAHASISWA LAMA DAN MAHASISWA BARU TERHADAP PENGGUNAAN SISTEM INFORMASI AKADEMIK (Studi Empiris pada Sistem Informasi Akademik (SIMAWEB) Fakultas Ekonomika dan Bisnis Universitas Diponegoro) - Melina Faridhana Harmoni; Indira Januarti (Diponegoro Journal of Accounting, 2019)
This study aimed to examine differences in perceptions of old and new students on the use of academic information system using DeLone and McLeane models (2003). There are five factors used in this research those are : content, accuracy, format, ease of use and timeliness.Variables used in this research are content, accuracy, format, ease of use and timeliness. This research uses survey method by questionnaire in collecting the data. The questionnaires are given to students faculty of economics and business Diponegoro University Semarang. Afterwards, the data gained is analysed using SPSS.The results of this research only the variable accuracy and timeliness that affect student’s perceptions of the use of information systems. While the variable content, format and ease of use doesn’t affect students’ perceptions of the use of information systems.